Unveiling spiritual violence: A critical discourse analysis of the Bidaah series - Sabiila, Diyanah Hanin; Arrahmah, Fathiyah Khasanah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the construction of spiritual violence in the Malaysian psychological religious drama series Bidaah through Norman Fairclough’s Critical Discourse Analysis (CDA) approach. Within the context of religious societies vulnerable to ideological domination based on religion, the series illustrates how religious discourse is employed as an instrument for legitimizing power and social control. This qualitative study uses purposive sampling to analyze eight selected scenes from five episodes containing dialogues and symbolic representations of religious authority within the fictional group Jihad Ummah. The textual analysis focuses on diction, sentence structure, modality, metaphor, and ideological presupposition to reveal the mechanisms of reproducing symbolic and epistemic violence that silence criticism and affirm the absolute authority of religious figures. The findings show that Bidaah not only represents religious violence narratively but also depicts social practices involving symbolic and structural violence that reflect the realities of religious conflict and polarization in Indonesia and Malaysia. This study contributes to a critical understanding of the relationship between language, power, and ideology in media, while opening space for reflection on repressive and exclusive religious practices in modern society. ***** Penelitian ini mengkaji konstruksi kekerasan spiritual dalam serial drama religi psikologis Malaysia, Bidaah, melalui pendekatan Analisis Wacana Kritis (AWK) Norman Fairclough. Dalam konteks masyarakat religius yang rentan terhadap dominasi ideologis berbasis agama, serial ini menampilkan bagaimana wacana keagamaan digunakan sebagai instrumen legitimasi kekuasaan dan kontrol sosial. Penelitian menggunakan metode kualitatif dengan purposive sampling, menganalisis delapan adegan terpilih dari lima episode yang memuat dialog dan simbolisasi kekuasaan religius dalam kelompok fiktif Jihad Ummah. Analisis teks difokuskan pada aspek diksi, struktur kalimat, modalitas, metafora, dan presuposisi ideologis untuk mengungkap mekanisme reproduksi kekerasan simbolik dan epistemik yang membungkam kritik dan meneguhkan otoritas absolut figur religius. Hasil penelitian menunjukkan bahwa serial Bidaah tidak hanya merepresentasikan kekerasan agama dalam bentuk naratif, tetapi juga memaparkan praktik sosial yang melibatkan kekerasan simbolik dan struktural, yang mencerminkan realitas konflik dan polarisasi keagamaan di Indonesia dan Malaysia. Penelitian ini berkontribusi pada pemahaman kritis tentang hubungan antara bahasa, kekuasaan, dan ideologi dalam media, sekaligus membuka ruang refleksi terhadap praktik keberagamaan yang represif dan eksklusif dalam masyarakat modern.